Efektivitas Pelayanan Pemberian Izin Mendirikan Bangunan Di Kantor Pelayanan Perizinan Terpadu Satu Pintu (Dpmptsp) Kota Makassar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to determine the effectiveness of services for granting building permits in the one-stop integrated licensing service office (DPMPTSP) in Makassar city. This study used a qualitative research  with a descriptive type. The number of informants in this study were 7 people who were determined by purposive sampling technique. Data collection techniques used observation, interviews and documentation. The results showed that regarding the optimization aspects of the objectives to be achieved by the Makassar City PTSP Service, it had provided services to the community by facilitating the form of management so that it was well served, the aspects of interaction between the organization and the surrounding environment related to the effectiveness of IMB services by the Makassar City PTSP Service certainly consisted of several methods such as, conducting awareness, capacitating, and empowering, and aspects of the role of individual behavior on effectiveness in an organization, namely how the Makassar City DPM-PTSP Service provided excellent service and becomed a stakeholder following community service SOPs. Keywords: Service effectiveness, granting building permits